Occurrences of sulphide minerals in the Stak and Tso Morari eclogites: Implications for the behaviour of sulphur and chalcophile elements in subduction zones - Riel, Nicolas; Hattori, Keiko; Guillot, Stephane; Latif, Mohamad; Kausar, Allah B (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1307 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.118